Anxiety Levels and Partner Dynamics in Women Across Reproductive Life Stages - Arika Melavi Swasti (Acta Psychologia, 2024)
This study examines anxiety levels and their relationship with partner dynamics in women of childbearing age and menopausal women. A comparative analysis was conducted utilizing standardized measures to assess anxiety levels, communication patterns, supportive behaviors, intimacy, and conflict resolution within intimate partnerships. The sample comprised 500 women of childbearing age and 500 menopausal women recruited from community-based settings. Results indicate that while women of childbearing age reported higher overall levels of anxiety, menopausal women exhibited greater variability in anxiety levels across different menopausal stages. Furthermore, significant differences were observed in communication patterns, perceived support from partners, intimacy, and conflict resolution between the two groups. Women of childbearing age reported more positive relationship dynamics characterized by open communication, perceived support, and greater intimacy, while menopausal women reported lower levels of perceived support and difficulties in communication and conflict resolution. These findings highlight the unique challenges and stressors faced by women at different reproductive life stages and underscore the importance of tailoring interventions to address the specific needs of women during reproductive transitions.